The Ion Channel ASIC2 is Required for Baroreceptor and Autonomic Control of the Circulation - Lu, Yongjun (2009)
Arterial baroreceptors provide a neural sensory input that reflexly regulates the autonomic drive of the circulation. Our goal was to test the hypothesis that a member of the acid sensing ion channel (ASIC) subfamily of the DEG/ENaC superfamily is an important determinant of the arterial baroreceptor reflex. We found that aortic baroreceptor neurons in the nodose ganglia and their terminals express ASIC2. Conscious ASIC2 null mice developed hypertension, had exaggerated sympathetic and depressed parasympathetic control of the circulation, and a decreased gain of the baroreflex, all indicative of an impaired baroreceptor reflex. Multiple measures of baroreceptor activity each suggests that mechanosensitivity is diminished in ASIC2- null mice. The results define ASIC2 as an important determinant of autonomic circulatory control and of baroreceptor sensitivity. The genetic disruption of ASIC2 recapitulates the pathological dysautonomia seen in heart failure and hypertension and defines a molecular defect that may be relevant to its development.